False air-bone gaps at 4 kHz in listeners with normal hearing and sensorineural hearing loss. (August 2013) - Margolis, Robert H.; Eikelboom, Robert H.; Johnson, Chad; Ginter, Samantha M.; Swanepoel, De Wet; Moore, Brian C. J.
Abstract Objective: This report presents data from four studies to examine standard bone-conduction reference equivalent threshold force levels (RETFL), especially at 4 kHz where anomalous air-bone gaps are common. Design: Data were mined from studies that obtained air- and bone-conduction thresholds from normal-hearing and sensorineural hearing loss (SNHL) participants, using commercial audiometers and standard audiometric transducers. Study sample: There were 249 normal-hearing and 188 SNHL participants. Results: (1) Normal-hearing participants had small air-bone gaps at 0.5, 1.0, and 2.0 kHz (‐1.7 to 0.3 dB) and larger air-bone gaps at 4 kHz (10.6 dB). (2) SNHL participants had small air-bone gaps at 0.5, 1.0, and 2.0 kHz (‐0.7 to 1.7 dB) and a larger air-bone gap at 4 kHz (14.1 dB). (3) The 4-kHz air-bone gap grew with air-conduction threshold from 10.1 dB when the air-conduction threshold was 5–10 dB HL to 21.1 dB when the air-conduction threshold was greater than 60 dB. (4) With the 4-kHz RETFL corrected by the average SNHL air-bone gap, the relationship between RETFL and frequency is linear with a slope of − 12 dB per octave. Conclusions: The 4-kHz air-bone gaps for listeners with SNHL could be avoided by adjusting the 4-kHz RETFL by − 14.1 dB.